The Effect of Price, Social Media Endorsement, and Place Atmosphere on Purchasing Decisions with Consumer Satisfaction as a Moderating Variable in Coffee Shop Consumers - Agustin, Tri; Suhardi, Suhardi; Firdaus, Rahmad; Hamdan, Hamdan (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study investigates the impact of price, social media endorsement, and venue atmosphere on purchase decisions, with consumer satisfaction as a moderating variable, within the context of coffee shop consumers in Pangkal Pinang, Indonesia. The research employs a quantitative approach using survey data collected from 200 respondents who meet specific criteria related to digital behavior and purchasing experience. Data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that while price does not significantly affect purchase decisions directly, it strongly influences consumer satisfaction, which in turn has a significant effect on purchase decisions. Social media endorsement exerts a direct and significant influence on both satisfaction and purchase decisions, underlining its strategic importance in contemporary digital marketing. Meanwhile, venue atmosphere significantly enhances satisfaction but shows limited direct impact on purchase decisions, confirming its mediating role through emotional experience. This research emphasizes the importance of integrated marketing strategies that combine pricing, influencer marketing, and atmospheric design to optimize consumer satisfaction and drive purchasing behavior in service-based industries.